2000
DOI: 10.1034/j.1399-6576.2000.440423.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia, recovery and postoperative nausea and vomiting after breast surgery. A comparison between desflurane, sevoflurane and isoflurane anaesthesia

Abstract: The quality of anaesthesia, time to opening of eyes and influence on respiration was similar with all three anaesthetics. As the emergence from anaesthesia did not differ significantly between the three agents, the choice of agent could be based on PONV rate and price. Desflurane had a significantly higher 24 h PONV rate than isoflurane. Early PACU PONV rate was significantly (P<0.05) lower for the more soluble isoflurane (4%) than for the low soluble gases, desflurane and sevoflurane together (28%). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…The incidence of nausea during the first 24 postoperative hours in group SF (68%) was almost comparable with that in previous reports of anesthesia without the use of prophylactic antiemetics (33%-85%) in major breast surgery [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Many factors are thought to be involved in the high incidence of PONV [18,21].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The incidence of nausea during the first 24 postoperative hours in group SF (68%) was almost comparable with that in previous reports of anesthesia without the use of prophylactic antiemetics (33%-85%) in major breast surgery [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Many factors are thought to be involved in the high incidence of PONV [18,21].…”
Section: Discussionsupporting
confidence: 88%
“…It has been recognized that major breast surgery is associated with a high incidence of PONV [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]18,21], and PONV is the major limiting factor for performing such surgery as a day procedure [11,21]. The incidence of nausea during the first 24 postoperative hours in group SF (68%) was almost comparable with that in previous reports of anesthesia without the use of prophylactic antiemetics (33%-85%) in major breast surgery [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to a study by Karlsenet al who reported a higher incidence of postoperative nausea/vomiting rate (24 hour in PACU and ward) with desflurane (67%) and sevoflurane (36%). [12] The combined approach of administering intraoperative opiates, local anesthesia, and NSAIDs is associated with significantly shorter discharge times, lower pain scores, and a lower incidence of nausea and vomiting, compared with traditional opiate-based anesthetic technique. Limitations of this study are due to its inherent design which does not permit a double-blind comparison of the two volatile anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, persistent nausea and vomiting can delay discharge from hospital (1,2). Breast surgery is associated with a high (40% to 70%) incidence of PONV (3,4).…”
Section: La Dexaméthasone Intraveineuse Permet-elle De Prévenir Les Nmentioning
confidence: 99%